2017
DOI: 10.1021/acs.jafc.7b00099
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Fish Oil Capsules: Polyunsaturated Fatty Acid Quantitation Plus Detection of Ethyl Esters and Oxidation

Abstract: Fish oils are the primary dietary source of ω-3 polyunsaturated fatty acids (PUFA), but these compounds are prone to oxidation, and commercial fish oil supplements sometimes contain less PUFA than claimed. These supplements are predominantly sold in softgel capsules. In this work, we show that Fourier transform (FT)-Raman spectra of fish oils (n = 5) and ω-3 PUFA concentrates (n = 6) can be acquired directly through intact softgel (gelatin) capsules. These spectra could be used to rapidly distinguish supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 47 publications
6
40
0
Order By: Relevance
“…The 10 products selected for analysis by the O3C represented over 80% of the Australian market, which overlaps considerably with the New Zealand market. The larger Bannenberg et al, 2017 study of >40 New Zealand samples [4], which we were aware of at the time and was cited in [2], showed results in full agreement with Nichols et al, 2016 [2], as does one further 2017 New Zealand study of 11 products [5] and a previous study of 15 products by Australia’s Therapeutic Goods Administration (TGA) [2]. …”
supporting
confidence: 78%
See 1 more Smart Citation
“…The 10 products selected for analysis by the O3C represented over 80% of the Australian market, which overlaps considerably with the New Zealand market. The larger Bannenberg et al, 2017 study of >40 New Zealand samples [4], which we were aware of at the time and was cited in [2], showed results in full agreement with Nichols et al, 2016 [2], as does one further 2017 New Zealand study of 11 products [5] and a previous study of 15 products by Australia’s Therapeutic Goods Administration (TGA) [2]. …”
supporting
confidence: 78%
“…As has been demonstrated by multiple studies, in marked contrast to Albert et al, 2015 [3], the majority of Australian and New Zealand fish oil products do meet their omega-3 label claims and are not oxidized as reported in four separate studies ([2,4,5] TGA: 2).…”
mentioning
confidence: 74%
“…However, the high non‐compliance rate reported by Albert et al has been challenged by others with particular criticism directed towards the analytical methods and types of fish oil products tested . Similarly, follow‐up studies found Australasian fish oil products to have a greater compliance, in terms of EPA + DHA and oxidation status, than previously reported . Many of the samples analyzed by Albert et al for example contained flavorings, often used to mask the “fishy” taste, or whose oils were pigmented.…”
Section: Resultsmentioning
confidence: 97%
“…Some reports have associated dietary PL with unique health benefits (Schuchardt et al, 2011;Tou, Jaczynski, & Chen, 2007). Commercial fish oils consist of TAG (or in some cases ethyl esters) (Killeen, Marshall, Burgess, Gordon, & Perry, 2017), whereas commercial krill oils are high in PL (Burri, Hoem, Monakhova, & Diehl, 2016;The United States Pharmacopeia Convention, 2014). However, the PL content of krill oil depends heavily on the extraction method used: Supercritical CO 2 extraction yields oils with almost no PLs (Yamaguchi et al, 1986), but the same solvent, mixed with a polar cosolvent (20% ethanol is used commercially) extracts oils that contain 28-52% PL (Burri et al, 2016;Catchpole, Moreno, Montañes, & Tallon, 2017;The United States Pharmacopeia Convention, 2014).…”
Section: Introductionmentioning
confidence: 99%